Quality of life metrics in terms of facilities and urban reputation: a case study in the city of Ventanilla, Lima Perú - Tapia Gallarday, Sashenka Flor (2023)
The availability and access to city facilities are key metrics in the assessment of the quality of life of its inhabitants. In our case study, it became evident that there is a gap between the supply of facilities (education, health, supply, security, culture, recreation, and sports) and the context of urban planning, which must structure a comprehensive and long-term vision through urban plans. This management tool must integrate facilities with housing, transportation, facilities, workplaces, etc. Likewise, it must cover various scales (neighborhoods, districts, municipalities, metropolitan areas, regions) and a multi stakeholder vision (government authorities, private entrepreneurs, academics, and civil society). The existing gap generates an inequitable territorial distribution of facilities and services, which leads to progressive social segregation in the city and a progressive decrease in the quality of life of its inhabitants. On the other hand, the concept of a city's reputation has two main connotations. On the one hand, it is based on the functional value that a city has for its inhabitants; on the other hand, it echoes the emotional ties between them and the city, according to social roots. This research addresses, from an empirical perspective, the supply of facilities within the city of Ventanilla and its influence on the city's reputation. The analysis was based on metrics of the spatial distribution of facilities and the perception of its inhabitants. The results show that the supply of facilities, within a decontextualized diagnosis of needs and without a long-term vision, through a Master Plan, causes a progressive deterioration of the quality of life. At the same time, quantitative metrics related to the provision of facilities can be a misleading approach to assessing the quality of life in a city. Our research made it clear that it is necessary to include metrics, methodologies, and qualitative analyses so that underlying issues such as accessibility, placemaking, and social cohesion are also assessed. Post -COVID-19 scenario concepts such as "the 15-minute city" and others may provide useful insights in this regard.